Kesesuaian Pola Ruang Pesisir Berbasis Data Terbuka Dan RTRW: Analisis Spasial-Statistik Di Kabupaten Demak - Rifqiya Luthfiyan; Adi Wibowo (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2026)
The suitability of spatial patterns in the coastal area of Demak Regency needs to be examined, as this area faces significant environmental pressures, particularly from coastal erosion, shoreline change, tidal flooding, and land subsidence. These conditions may lead to inconsistencies between the spatial pattern directives in the Regional Spatial Plan (RTRW) and the actual land use conditions on the ground. This study aims to analyze the suitability of spatial patterns in the coastal area of Demak Regency in relation to the RTRW directives stipulated in regional regulations, and to identify spatial patterns of land-use incompatibility. This research integrates OpenStreetMap (OSM) data, the Demak Regency RTRW map, administrative boundaries, and shoreline data using a Geographic Information System (GIS) approach. The analysis was conducted using overlay intersection to compare planned spatial functions and actual land use, supported by the Chi-Square test, the Kappa coefficient, Moran’s I, and Local Indicators of Spatial Association (LISA). The results show that the direct suitability between RTRW and actual land use is only 5.8%. The Kappa value of 0.0361 indicates a very low level of spatial agreement between the spatial plan and actual conditions. The Chi-Square test yielded χ² = 42,073.37 (p < 0.001), indicating a significant relationship between RTRW categories and actual land use, although the level of suitability remains low. Spatial autocorrelation analysis produced a Moran’s I value of 0.024 with p < 0.01, indicating a very weak but statistically significant positive spatial autocorrelation. The LISA results identified local clusters of incompatibility in protected areas, settlements, and coastal aquaculture zones. These findings indicate that the implementation of the Demak Regency RTRW faces spatial gaps caused by coastal environmental pressures and socio-economic dynamics. Therefore, spatial planning needs to be updated through a more adaptive approach that responds to coastal environmental changes.